Pain Perception, Personality Trait and Attitude toward Orthodontic Treatment among the Patients Visiting at the Tertiary Care Hospital Jamshoro - Dodani, Murk; Abdul Jabbar; Sahito, Ashique Hussain; Saeed, Bushra; Andani, Karishma; Dodani, Sindhu (Indus Journal of Bioscience Research, 2025)
Introduction: Pain perception and psychological readiness significantly influence orthodontic treatment outcomes. Individual differences in personality traits can impact how patients experience pain and respond to treatment protocols. Objective: To assess the frequency of pain perception, personality traits, and attitude toward orthodontic treatment among patients visiting a tertiary care hospital in Jamshoro. Materials and Methods: A cross-sectional study was conducted from February, 2025 to May, 2025.at the Orthodontic Department, Liaquat University of Medical and Health Sciences, Jamshoro. A total of 295 patients aged 15–25 undergoing fixed orthodontic treatment were assessed using validated questionnaires, including the Visual Analogue Scale (VAS) for pain, NEO-Five Factor Inventory for personality, and Likert-scale for attitude. Data were analyzed using SPSS version 26. Results: Moderate pain was reported by 46.4% of participants. Positive attitude was observed in 69.2%, and 70.5% had good-to-excellent personality profiles. Significant associations were found between personality traits, pain levels, and treatment attitude. Conclusion: Personality traits influence the perception of pain and the disposition towards treatment, influencing compliance and satisfaction.